Metode Story Telling dan Role Play untuk Reduksi Stress ADHA (Story Telling and Role Play Methods for ADHA Stress Reduction) - Broto, Germino Wahyu; Rini, Afinia Sandhya (Happiness: Journal of Psychology and Islamic Science, 2024)
Children with HIV/AIDS (ADHA) tend to be affected by social discrimination from the environment in which they live. The social discrimination experienced is always repeated. This is because ADHA are often ostracized, often receive negative stigma, and are often neglected. This social discrimination makes ADHA feel easily stressed. Therefore, efforts are needed to overcome the stress problems experienced by ADHA. Efforts that can be made include using the story telling method and role playing. The novelty of this research lies in the use of story telling and role play methods in an integrated manner. This research aims to determine the extent to which story telling and role playing treatment can reduce stress in HIV/AIDS children in Tulungagung Regency. The research design used is a Mix Method Explanatory Sequential Design approach, with two sequential or interactive sequential phases. The first stage carried out quantitative data collection and analysis as a priority to answer research questions. The next stage of qualitative data collection is carried out following the previous phase. The subjects of this research were children with HIV/AIDS who experienced stress and entered the concrete operational and formal operational cognitive development phase (7 to 17 years) with a sample of 15 children. The measuring tool used is the Perceived Stress Scale (PSS) questionnaire with 10 question items (PSS-10) and 2x story telling therapy. The research results obtained show that t count is 6.6647 > t table 2.145 so that providing treatment to children with HIV/Aids using a combination of story telling and role play can reduce stress levels significantly.